2015
DOI: 10.5761/atcs.oa.13-00271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Optimal Visceral Branch Configuration in Open Thoracoabdominal Aortic Repair by Computed Tomography

Abstract: IntroductionSurgical treatment for Crawford type II-IV thoracoabdominal aneurysms (TAAAs) that require branch reconstruction of the visceral and RAs has been challenging because of the technical complexity and surgical invasiveness. In particular, reducing/avoiding perioperative spinal ischemia, renal failure, respiratory failure, and bleeding complications are important factors for surgical success. [1][2][3][4] In our institution, several modifications have been performed in terms of perioperative spinal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Kulik et al 17 reported excellent results using such a multibranched strategy together with the use of an interposition prosthesis in 57% of cases. 18 The hybrid technique combining open and endovascular surgery is another method which has been used in patients with T4AAA or SRAAA. The hybrid technique has been presented as supposedly less invasive as it eliminates the risk of aortic cross clamping.…”
Section: Discussionmentioning
confidence: 99%
“…Kulik et al 17 reported excellent results using such a multibranched strategy together with the use of an interposition prosthesis in 57% of cases. 18 The hybrid technique combining open and endovascular surgery is another method which has been used in patients with T4AAA or SRAAA. The hybrid technique has been presented as supposedly less invasive as it eliminates the risk of aortic cross clamping.…”
Section: Discussionmentioning
confidence: 99%
“…Late occlusion involves VVs at different rates, with a significant prevalence of renal arteries compared to other vessels. Renal branch occlusion has been observed in 8-9.6% of cases at midterm follow-up [7,28]. Along with the high individual anatomic variability of the renal artery angle compared with other VVs, additional factors-e.g., respiratory motion and small vessel size-could have an adjunctive stress effect on stents.…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of different devices employed in VV endovascular reconstruction has not been confirmed in a multicentric series [7], while the mean artery length and anatomic location were considered more likely associated with a poor branch outcome, and this finding could be a touchpoint with possible mechanical factors influencing observed late fate of LRA after open repair-particularly when presewn grafts are used [28].…”
Section: Discussionmentioning
confidence: 99%
“…7 The mean artery length and anatomic location were considered more likely to be associated with a poor branch outcome, and this finding could be a touchpoint with possible mechanical factors influencing the observed late fate of LRA after open repair, particularly when presewn grafts are used. 28…”
Section: Discussionmentioning
confidence: 99%